Biological leaching of Mn, Al, Zn, Cu and Ti in an anaerobic sewage sludge effectuated by Thiobacillus ferrooxidans and its effect on metal partitioning - Lombardi, A. T.; Garcia, O. (Elsevier B.V., 2002)
The chemical fractionation and bioleaching of Mn, At, Zn, Cu and Ti in municipal sewage sludge were investigated using Thiobacillus ferrooxidans as leaching microorganism. As a result of the bacterial activity, ORP increase and pH reduction were observed. Metal solubilization was accomplished only in experimental systems supplemented with energy source (Fe(II)). The solubilization efficiency approached similar to80% for Mn and Zn, 24% for Cu, 10% for At and 0.2% for Ti. The chemical fractionation of Mn, At, Zn, Cu and Ti was investigated using a five-step sequential extraction procedure employing KNO3. KF, Na4P2O7, EDTA and HNO3. The results show that the bioleaching process affected the partitioning of Mn and Zn, increasing its percentage of elution in the KNO3 fraction while reducing it in the KF, Na4P2O7 and EDTA fractions. No significant effect was detected on the partitioning of Cu and Al. However, quantitatively the metals Mn, Zn, Cu and At were extracted with higher efficiency after the bacterial activity. Titanium was unaffected by the bioleaching process in both qualitative and quantitative aspects. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: metal speciation; metal partitioning; sewage sludge; bioleaching; T. ferrooxidans